2021
DOI: 10.1021/acs.orglett.1c01156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Imidazole-Based [30]Heptaphyrin and Stable Figure-Eight [60]Tetradecaphyrins via [5 + 2] Condensations in One Pot

Abstract: Derived from a Pd-catalyzed oxidative C–H/C–H coupling reaction, two giant imidazole-based [60]­tetradecaphyrins adopting stable figure-eight geometry together with one [30]­heptaphyrin are obtained by [5 + 2] MacDonald condensations in one pot. The directional imidazole is believed to play a vital role for the diverse cyclization and conformation stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This approach was highlighted by a recent report by Gao, You et al who successfully synthesized an imidazole-embedded expanded porphyrinoid, [60]tetradecaphyrin 5 (Figure 4). [22] Enantiomers (M,M)-5 and (P,P)-5 were effectively separated using chiral HPLC (Daicel, Chiralpak IA). This represented the largest expanded porphyrinoid to be successfully separated into its enantiomers to date.…”
Section: Chiral Resolution Of Expanded Porphyrinoids In the Freebase ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was highlighted by a recent report by Gao, You et al who successfully synthesized an imidazole-embedded expanded porphyrinoid, [60]tetradecaphyrin 5 (Figure 4). [22] Enantiomers (M,M)-5 and (P,P)-5 were effectively separated using chiral HPLC (Daicel, Chiralpak IA). This represented the largest expanded porphyrinoid to be successfully separated into its enantiomers to date.…”
Section: Chiral Resolution Of Expanded Porphyrinoids In the Freebase ...mentioning
confidence: 99%
“…This oxidative-type NFR was found to give rise to macrocycle 21, which incorporates an unprecedented aza [5]helicene motif within the expanded carbaporphyrin scaffold. In the presence of BF 3 • Et 2 O, a subsequent NFR afforded a more complicated structure (22), with a bidirectional heptacyclic S-shaped helicene ribbon (Figure 18). [40] Racemic mixtures of the two topologically chiral helicenophyrinoids 21 and 22 could be separated into their enantiomers by HPLC using a chiral stationary phase (Chirex 1030).…”
Section: Chiral Resolution Of Expanded Porphyrinoids Based On Scaffol...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing implementation of nuclear reactors, reprocessing of the spent nuclear fuel has become a hot topic and has attracted increasing attention. The uranyl ion ([UO 2 ] 2+ ) accounts for approximately 90% of the metal ions of the nuclear waste liquid and exists stably in the natural environment; thus, its recycling is very important toward a sustainable application of nuclear power. Therefore, it is of great significance to investigate uranyl­(VI) complexes and their stability to understand the chemical transformation and migration of nuclear waste and coordination chemistry in spent nuclear fuel recycling. The rich and varied coordination chemistry of actinide has made these species of interest from the perspective of ligand design, electronic structure, and theory. , On the other hand, understanding the bonding and coordination environments in actinide complexes could help in the future design of extractants for target actinide elements that could be relevant to the development of the nuclear industry or the remediation of the spent nuclear fuel …”
Section: Introductionmentioning
confidence: 99%
“…To achieve chiral resolution, structural rigidification by means of (non)metal coordination or scaffold modification, e.g., N-fusion, N-methylation, and installation of a central chirality unit, is indispensable. In spite of these important findings, it is worth noting that direct enantiomeric separation of expanded porphyrins in their free-base form has remained an aspirational but elusive target for the past decades. , A perusal of the literature revealed that some enantiomers racemize even at room temperature, , thus further underscoring challenges in this field.…”
mentioning
confidence: 99%